Social economic life of oil palm farmers - Rahmanita Rahmanita; Fatmariza Fatmariza; Buchari Nurdin (International Conferences on Educational, Social Sciences and Technology)
Socio-economic conditions of oil palm farmers will affect the income and education of children. The purpose of this study to describe socio-economic life of oil palm farmers since 1996-2016 and their changes of life, and their developmental impact on the education of Jorong Silawai children. This study uses historical research methods, namely Heuristik, source criticism, interpretation, and Histroriografi. The results of the study found that the impact of the presence of oil palm companies on the economic condition is very influential that after the existence of the company than before the company. Oil palm farmers who previously farmed to meet their daily needs, with PT BTN's plasma plantations could be an additional source of additional farming. Revenues from PT BTN's plasma plantations are varied. The main factors that influence it are fluctuations in palm oil prices. Oil palm growers also get producers from other work. Revenue from PT BTN's plasma plantations is not possible to fulfill their life. The low awareness of farmers on the education of their children. Here is demanded the role of government in improving socio-economic conditions of oil palm farmers so that it will have an impact on the awareness of farmers on the education of their children.